2022
DOI: 10.1002/ange.202116220
|View full text |Cite
|
Sign up to set email alerts
|

Oriented Nanoarchitectonics of Bacteriorhodopsin for Enhancing ATP Generation in a FoF1‐ATPase‐Based Assembly System

Abstract: Energy conversion plays an important role in the metabolism of photosynthetic organisms. Improving energy transformation by promoting a proton gradient has been a great challenge for a long time. In the present study, we realize a directional proton migration through the construction of oriented bacteriorhodopsin (BR) microcapsules coated by F o F 1 -ATPase molecular motors through layer-by-layer (LBL) assembly. The changes in the conformation of BR under illumination lead to proton transfer in a radial direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…ATP synthase-catalyzed ATP formation is the biocatalytic molecular machine providing significant amounts of ATP which are synthesized and needed daily by biological organisms [ 110 , 111 ]. Although the exploration of various artificial stimuli-responsive biocatalytic ATP synthesis systems is attractive [ 112 ] (for example, proteoliposome systems containing oriented bacteriorhodopsin and using light for proton gradient generation to drive the formation of ATP [ 113 ]), further improvements of rate and stability of ATP production achieved by these approaches are needed. Therefore, industrial large- scale production utilizes Corynebacterium ammoniagenes whole cells for the biotransformation of adenine and inorganic phosphate to ATP [ 114 ].…”
Section: Synthesis Of Biologically Active Phosphometabolitesmentioning
confidence: 99%
“…ATP synthase-catalyzed ATP formation is the biocatalytic molecular machine providing significant amounts of ATP which are synthesized and needed daily by biological organisms [ 110 , 111 ]. Although the exploration of various artificial stimuli-responsive biocatalytic ATP synthesis systems is attractive [ 112 ] (for example, proteoliposome systems containing oriented bacteriorhodopsin and using light for proton gradient generation to drive the formation of ATP [ 113 ]), further improvements of rate and stability of ATP production achieved by these approaches are needed. Therefore, industrial large- scale production utilizes Corynebacterium ammoniagenes whole cells for the biotransformation of adenine and inorganic phosphate to ATP [ 114 ].…”
Section: Synthesis Of Biologically Active Phosphometabolitesmentioning
confidence: 99%
“…8 In a very recent report, Li et al elegantly reported the coreconstitution of oriented bR and ATP synthase into microcapsules. 10 Using a bR to ATP synthase ratio of ∼800, they calculated a total amount of 4500 nmol of ATP synthesized per hour per milligram of ATP synthase. With coreconstituted pR-SpyC-MBP and F 1 F O ATP synthase, we find a similar amount of 3800 ± 500 nmol per hour per mg of ATP synthase despite using ∼40 times less pR per ATP synthase (20:1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The coreconstitution of ATP synthase with the archaeal analogue bacteriorhodopsin (bR) was a seminal experiment by Racker and Stoeckenius to support Peter Michells’ hypothesis of chemiosmosis , and has since been used as a minimal light-driven system to energize a variety of processes in bottom-up synthetic assemblies. , This success is significantly owed to the fact that uncontrolled reconstitution of bR into preformed liposomes mainly yields a population acidifying the liposomal lumen by pumping protons to the inside, ,, which is required for ATP synthesis on the outside of the liposomes, from where ATP can diffuse to its consumption sites. Drawbacks of bR are its poor heterologous expression and cumbersome molecular biology techniques in the native archaeal host Halobacterium salinarium .…”
Section: Introductionmentioning
confidence: 99%
“…The structure and work mechanism of F O F 1 -ATPase have been revealed experimentally and theoretically. In addition, the reconstitution of F O F 1 -ATPase on the cell-mimic polymer multilayer microcapsules has been performed, in which ATPase retains its biological activity ( 5 ). These F O F 1 -ATPase–functionalized polymer capsules can serve as an excellent model to study the synthesis and regulation of ATP on demand.…”
Section: Introductionmentioning
confidence: 99%